NEW APPROACHES TO PRIMARY EDUCATION TEACHER TRAINING - Mukhtarali Sultanov; Nodira Mukhiddinova; Ulbosin Sultanova; Lazzat Saidaliyeva (The Bioscan, 2024)
Pedagogy is the most important in the system of sciences related to the development and formation of a person as an individual. For such formation is practically impossible without education as a purposeful process of interaction with a child, transferring social experience to him. Based on the achievements of all sciences about man, pedagogy studies and develops the most optimal ways of formation of a person, his upbringing and education.